Optimized Production of Bacteriocin by Lactobacillus plantarum Isolated from Fermented Maize (Ogi) - Aghemwenhio, Itohan Sandra; Omonigho, Solomon Esharegoma (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
Bacteriocins, potent antimicrobial peptides synthesized by lactic acid bacteria (LAB), are primary metabolites with ribosomal origins. Their extensive inhibitory range indicates their role as food preservatives and their ability to fight human pathogens. This research focused on enhancing bacteriocin yield from genetically confirmed LAB strains derived from fermented maize (Ogi). The study investigated the influence of various nutrients and pH levels on bacteriocin activity. White and yellow maize samples (500g each) were sourced from Oba Market in Benin City and the International Institute of Tropical Agriculture (IITA) in Nigeria. Established microbiological techniques were used to isolate eight Lactobacillus plantarum strains from the maize fermented into ogi. These strains were further identified through molecular techniques, specifically the amplification of 16S rDNA genes Polymerase Chain Reaction (PCR). Bacteriocin presence was assessed via agar spot tests and well diffusion methods. The effect of enzymes, different growth media and vitamins were determined to optimize bacteriocin production. The study aimed to determine the optimal medium composition for bacteriocin production. Molecular identification through PCR amplification of 16S rDNA genes verified the LAB strains as Lactobacillus plantarum (TM 229), Lactobacillus plantarum (TM 224), and Lactobacillus fermentum (TM 217). These strains produced different levels of bacteriocin, 6500 AU/ml (TM 229), 3700 AU/ml (TM 224), and 3200 AU/ml (TM 217) at a pH of 6.5. TM 229 yielded 8800Au/ml when treated with maltose compared with control of 6500Au/ml The findings suggest further study on bacteriocin optimization is recommended.